Cultural Analysis Of The Ma'baca Prayer Tradition - Puteri Padriani Paris*; Mariesa Giswandhani (Riwayat: Educational Journal of History and Humanities, 2023)
This research aims to analyze the intercultural communication of ma'baca doa salama' tradition in Lumpue Village, Pare-Pare City. The analysis used is descriptive qualitative by conducting interviews, observations, and literature studies. Data analysis is done by reduction or sorting, presentation, and conclusion formulation. Based on the research results, it shows that: 1. The people of Lumpue Village carry out the ma'baca doa salama' tradition with several traditional processes of the community who always hold the ma'baca doa salama' ritual at the feast day celebration because they respect the ancestors who have been passed down from generation to generation and do not eliminate the identity that has been carried out. Such as preparing a menu of dishes to call the elders in the village. The people of Lumpue Village carry out the tradition of ma'baca doa salama' because firstly because the thinking of the people in the area is still fairly traditional and holds noble values of ancestral heritage, they believe that by doing this habit, it will bring goodness to their lives and beliefs involve "kindness" (appreciation) or love. 2. The meaning of ma'baca doa salama' on holiday celebrations in Lumpue Village is ma'baca doa salama' for people who have died, the salvation of the world and the hereafter, as a form of gratitude to God, the belief of the people of Lumpe Village if they do not carry out the tradition of ma'baca doa salama' then it will be a form of gratitude to God.